2017
DOI: 10.1097/dcr.0000000000000834
|View full text |Cite
|
Sign up to set email alerts
|

What To Do With Lateral Nodal Disease in Low Locally Advanced Rectal Cancer? A Call for Further Reflection and Research

Abstract: Chemoradiotherapy with total mesorectal excision might not be sufficient in a selected group of patients. Further research is needed about which pretreatment features of the lateral nodes predict local recurrence and what is needed to prevent these from developing. See Video Abstract at http://links.lww.com/DCR/A338.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
79
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 86 publications
(84 citation statements)
references
References 14 publications
3
79
2
Order By: Relevance
“…One study of 116 patients with ypN+ disease reported lateral pelvic recurrence rates of 35·7 and 87·5 per cent respectively when enlarged LLNs had a short‐axis diameter of 5–9·9 mm and 10 mm or more. Similar data have been reported from the West, with a recent study finding a lateral local recurrence rate of 33·3 per cent at 4 years when LLNs had a short‐axis diameter of 10 mm or above. A recent multi‐institutional international retrospective study from 12 institutions reported that patients with LLNs and a short‐axis diameter of at least 7 mm had a significantly higher risk of lateral local recurrence than patients with LLNs of less than 7 mm.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…One study of 116 patients with ypN+ disease reported lateral pelvic recurrence rates of 35·7 and 87·5 per cent respectively when enlarged LLNs had a short‐axis diameter of 5–9·9 mm and 10 mm or more. Similar data have been reported from the West, with a recent study finding a lateral local recurrence rate of 33·3 per cent at 4 years when LLNs had a short‐axis diameter of 10 mm or above. A recent multi‐institutional international retrospective study from 12 institutions reported that patients with LLNs and a short‐axis diameter of at least 7 mm had a significantly higher risk of lateral local recurrence than patients with LLNs of less than 7 mm.…”
Section: Discussionsupporting
confidence: 85%
“…In contrast, in Western countries, neoadjuvant (C)RT protocols are mostly employed, resulting in local recurrence rates of less than 10 per cent, with minimal indication for LLND. Recently, however, Eastern and Western studies have suggested that (C)RT and TME without LLND may not be sufficient in patients with enlarged LLNs, with a lateral pelvic recurrence rate of 19·5 per cent in patients with LLNs 7 mm or more in size.…”
Section: Introductionmentioning
confidence: 99%
“…Several Korean centres (that do not perform LLND) have shown increased local recurrence rates in patients with enlarged lateral lymph nodes on preoperative staging treated with neoadjuvant (chemo)radiotherapy and TME, suggesting this may be insufficient for adequate disease control. A recent small UK series suggested similar trends, with a high lateral local recurrence rate in patients with a lymph node short axis larger than 10 mm. In enlarged nodes, the combination of neoadjuvant chemoradiotherapy (CRT) and LLND in a Japanese series resulted in low local recurrence rates and good disease‐free survival, suggesting that lateral nodal disease is a local problem that can be cured.…”
Section: Introductionmentioning
confidence: 94%
“…Chemoradiation therapy without LPLND among patients with lateral compartment lymph nodes[10 mm on short axis risks local failures in 33.3%. 6 However, when followed by selective LPLND for patients with lymph nodes greater than 7-8 mm is associated with a low risk (0.9-3.4%) of lateral compartment failure with an incidence of pathologically confirmed persistent lateral node involvement in more than half the dissected patients. 7,8 Although the jury has not determined whether the decision of dissection may be made after evaluation of the posttreatment response, a selective LPLND strategy has the potential to identify the few patients who may benefit from LPLND and safely avoid it in nearly all other patients.…”
mentioning
confidence: 99%